Development of Islamic Nusantara Course Module at Universitas Nahdlatul Ulama Blitar - Siti Uswatun Kasanah; M. Subhan Ansori (Journal of Development Research, 2019)
The purpose of this research is to knowing out the availability of Nusantara Islamic course modules at the Universitas Nahdlatul Ulama Blitar and how develop an Islamic Nusantara course module at the Universitas Nahdlatul Ulama Blitar.The focus of this research is the development of the Islamic Nusantara course module at University that did not exist previously. Using the Research and Development method developed by Borg and Gall which includes preliminary studies, planning research, design development, product testing, revised limited field test results, extensive product testing, revised field test results more broadly, the due diligence, the final revision of the feasibility test results, dissemination and implementation of the final product. Data was collected from the assessment of two experts7through the Expert validation sheet and 60 student respondents through the student respondent questionnaire. Data analysis uses qualitative and quantitative approach techniques. Data in the form of suggestions and criticisms from experts/experts and students are analyzed with a qualitative approach, while module feasibility data and opinions regarding module suitability are processed with a quantitative descriptive approach. The analysis that at the Universitas Nahdlatul Ulama Blitar there is no Nusantara Islamic course module available even though there is a Nusantara Islamic course, so development is needed.The results of the study showed that the module was suitable to be used as teaching material in the Islamic Nusantara course. This is based on material validation of 91.96 (very good), language and pictures of 90.75 (very good), presentation of 88.66 (very good), display of 94.53 (very good) as well as student responses with an average score of 86.6 (very good). Some suggestions from experts include changes to the sub themes of the 2 modules, and caver design. While suggestions from students should be corrected for incorrect writing.